(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Aim:This study investigates how social media content and perceived risk influence tourists’ visit intention, mediated by ecotourism destination image. Materials and Methods: A quantitative causal design was employed, collecting data from 315 tourists via questionnaires, analyzed using PLS-SEM. Results and discussions:Social media content and perceived risk significantly affect visit intention directly and indirectly through destination image, which acts as a strong mediator. Notably, well-managed risk perception positively enhances destination evaluation and intention. Conclusions:Destination managers should leverage engaging social media and transparent risk communication to boost ecotourism destination image and tourist visits.